Blue thermally-induced delayed fluorescence polymer as well as preparation method and application thereof

By designing a blue heat-induced delayed fluorescent polymer with diphenyl silicon and TADF luminescence units directly connected, the problem of low efficiency of blue TADF OLED devices is solved, achieving efficient blue emission and simplified preparation process, suitable for large sizes and flexibility Display the application.

CN119143972AActive Publication Date: 2024-12-17CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411493407.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-17
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The development of existing blue thermally induced delayed fluorescence (TADF) polymers is lagging behind, resulting in low efficiency and complex production of blue TADF OLED devices, making it difficult to achieve efficient blue emission.

Method used

A blue heat-induced delayed fluorescent polymer with a specific structure was designed, directly connected to the TADF luminescence unit through diphenyl silicon, combined with sp3 hybrid silicon atoms and alkyl substituents, to increase the triplet energy level and reduce the single The energy level difference between heavy and triplet states enhances molecular rigidity to inhibit non-radiative transitions.

Benefits of technology

It realizes efficient blue heat-induced delayed fluorescence emission, improves fluorescence quantum efficiency, and simplifies the polymer preparation process, suitable for solution processing and industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100657230000021
    Figure BDA0005100657230000021
  • Figure BDA0005100657230000022
    Figure BDA0005100657230000022
  • Figure BDA0005100657230000031
    Figure BDA0005100657230000031
Patent Text Reader

Abstract

The invention relates to the field of organic light-emitting materials, in particular to a blue thermally induced delayed fluorescence polymer as well as a preparation method and application thereof. According to the polymer with the structure shown in the formula 1, diphenyl silicon of the polymer is directly connected with acridine in a TADF light-emitting unit, sp3 hybridized silicon atoms can effectively break conjugation of a main chain of the polymer, and the triplet energy level is improved. When an alkyl substituent group is introduced to the ortho-position of a connecting site of diphenyl silicon and a TADF unit, the torsion angle of an aromatic ring can be increased, the triplet energy level is further improved, the energy level difference between the singlet state and the triplet state is reduced, and meanwhile, the increase of molecular rigidity inhibits non-radiative transition. Experimental results show that the polymer not only has a high triplet energy level, but also has high fluorescence quantum efficiency, and presents efficient blue thermally induced delayed fluorescence emission. In addition, the preparation method of the polymer provided by the invention is simple, and the obtained polymer has excellent solubility and film-forming property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic luminescent materials, in particular to a blue thermally induced delayed fluorescence polymer and a preparation method and application thereof. Background Art

[0002] Thermally induced delayed fluorescence (TADF) materials have a small singlet-triplet energy level difference (ΔE ST ), triplet excitons can be converted into singlet excitons through the reverse intersystem crossing process to radiate light, achieving 100% exciton utilization and effectively improving the efficiency of organic electroluminescent devices (OLEDs). Compared with phosphorescent complexes, TADF materials are pure organic compounds, which are easier to control the luminescence properties through structural design and modification. At the same time, no precious metals are required, which is more beneficial to the commercial application of devices. Since Professor Adachi of Kyushu University in Japan made a breakthrough in the molecular design and device application of organic TADF materials in 2012, this field has attracted widespread attention from academia and industry at home and abroad. A large number of TADF luminescent materials have been reported one after another, and the corresponding device performance even exceeds that of phosphorescent OLEDs. Among them, TADF small molecule materials have carefully controlled and optimized the device manufacturing process through vacuum evaporation technology, showing excellent performance. However, strict processing conditions increase the complexity of device production, bring challenges to the manufacture of high-resolution and large-area devices, and increase the cost of product production.

[0003] Polymers have good solubility and film-forming properties. When used as luminescent materials in electroluminescent devices, they can be prepared using simple solution processing methods such as spin coating, inkjet printing, and printing. They have great application potential in large-size and flexible displays. At present, green to red TADF OLED devices have achieved satisfactory device performance, and the external quantum efficiency has exceeded 25%. However, the development of blue TADF polymers is still far behind. As one of the three primary color materials, blue light materials are necessary luminescent materials for realizing full-color, high color rendering index OLED devices. Therefore, it is crucial to develop efficient blue thermally induced delayed fluorescence polymers.

[0004] Currently, TADF polymers are mainly constructed by incorporating donor and acceptor units into the polymer backbone or side chains. The strong interaction between the donor and acceptor units reduces the energy level of the singlet state, resulting in a redshift of the emission spectrum, which complicates blue emission. At the same time, the triplet energy level of the blue TADF luminescent unit is usually higher than that of the conjugated backbone of the main-chain TADF polymer, which makes it impossible to prevent the reverse transfer of triplet energy from the TADF unit to the backbone, thus causing non-radiative recombination in the backbone. Although the design of non-conjugated backbone side-chain TADF polymers can effectively solve this problem, the insulation of the non-conjugated backbone itself significantly limits the device performance of OLEDs. Another problem with blue TADF polymers is the accumulation of long-lived triplet excitons, which makes the excitons more vulnerable to the annihilation process, thus having a negative impact on the device efficiency. Therefore, how to obtain a polymer with a simple synthesis method and high photoluminescence efficiency to achieve efficient blue TADF emission is the technical problem to be solved currently. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a blue thermally activated delayed fluorescence polymer, its preparation method and application. The blue thermally activated delayed fluorescence polymer provided by the present invention has blue TADF emission and high luminescence efficiency.

[0006] The present invention provides a blue thermally activated delayed fluorescence polymer having a structure of Formula 1:

[0007]

[0008] Wherein, the R1 and R3 are independently selected from C6-C 30 aryl;

[0009] The R2 and R4 are independently selected from H or C1-C8 alkyl;

[0010] The R5, R6 and R7 are independently selected from C1-C 20 alkyl or C6-C 30 aryl;

[0011] The A is selected from C6-C aryl having an electron-withdrawing ability; 50 aryl;

[0012] The n is 2-200;

[0013] 0 < x < 0.5; preferably 0.01 ≤ x < 0.5.

[0014] The blue thermally induced delayed fluorescent polymer of the present invention may have a capping group or may not have a capping group. In certain embodiments of the present invention, if the blue thermally induced delayed fluorescent polymer of the present invention has a capping group, it is a blue thermally induced delayed fluorescent polymer having a structure of Formula 1-a;

[0015]

[0016] Wherein, the R1 to R7, A, x and n are the same as those described above and are not described in detail; the R0 is a capping group. In one embodiment of the present invention, the capping group is a phenyl group, a thienyl group or a pyridyl group, preferably an unsubstituted phenyl group.

[0017] The R1 and R3 of the present invention are independently selected from C6 to C 30 Preferably, R1 and R3 are independently selected from unsubstituted C6 to C 30 Aromatic group, or C1~C 20 Alkyl and C1~C 20 At least one substituted C6-C 30 More preferably, R1 and R3 are independently selected from phenyl, tolyl, ethylphenyl, butylphenyl, hexylphenyl, octylphenyl, methoxyphenyl or dimethylaminophenyl. In certain embodiments of the present invention, R1 and R3 are the same. In certain embodiments of the present invention, R1 and R3 are both phenyl.

[0018] The R2 and R4 of the present invention are independently selected from H or C1-C8 alkyl. Preferably, the R2 and R4 are independently selected from H, methyl, ethyl, propyl, butyl, pentyl or hexyl. In certain embodiments of the present invention, the R2 and R4 are the same. In certain embodiments of the present invention, the R2 and R4 are both methyl. In the present invention, when the R2 and R4 are both methyl, the torsion angle between the diphenylsilicon and the acridine ring is increased, the conjugation degree of the donor group of the light-emitting unit is reduced, and the triplet energy level of the main chain is increased; at the same time, the molecular rigidity is increased, the non-radiative transition is effectively weakened, and the photoluminescence quantum yield (PLQY) will be greatly improved.

[0019] The R5 of the present invention is selected from C1 to C 20 Alkyl or C6~C 30 Preferably, R5 is selected from unsubstituted C1 to C 20 Alkyl, unsubstituted C6~C 30 Aromatic group, or C1~C 20 Alkyl and C1~C 20 At least one substituted C6-C 30More preferably, R5 is selected from hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, butylphenyl, hexylphenyl, octylphenyl, decylphenyl, undecylphenyl, tridecylphenyl, heptadecylphenyl, hexyloxyphenyl, octyloxyphenyl, decyloxyphenyl, undecyloxyphenyl, tridecyloxyphenyl or heptadecyloxyphenyl.

[0020] The R6 and R7 of the present invention are independently selected from C1 to C 20 Alkyl or C6~C 30 Preferably, R6 and R7 are independently selected from unsubstituted C1 to C 20 Alkyl, unsubstituted C6~C 30 Aromatic group, or C1~C 20 Alkyl and C1~C 20 At least one substituted C6-C 30 More preferably, R6 and R7 are independently selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl, methylphenyl, butylphenyl, hexylphenyl, octylphenyl, decylphenyl, methoxyphenyl, hexyloxyphenyl, octyloxyphenyl or decyloxyphenyl. In certain embodiments of the present invention, R6 and R7 are the same. In certain embodiments of the present invention, R6 and R7 are both selected from n-hexyl (-C6H 13 ).

[0021] The A of the present invention is selected from C6~C 50 Preferably, A is a C6-C 50 More preferably, A is a C6-C 30 More preferably, A is selected from a group having a structure of formula Aa;

[0022]

[0023] Wherein, R8 is selected from unsubstituted triazine group, cyano substituted triazine group, trifluoromethyl substituted triazine group, C1~C 20 Alkyl-substituted triazine, C6~C 30 Aromatically substituted triazine radicals, unsubstituted pyrimidinyl radicals, cyano-substituted pyrimidinyl radicals, trifluoromethyl-substituted pyrimidinyl radicals, C1-C 20 Alkyl-substituted pyrimidinyl, C6~C 30 aromatic substituted pyrimidinyl, unsubstituted pyridyl, cyano substituted pyridyl, trifluoromethyl substituted pyridyl, C1~C 20 Alkyl substituted pyridyl, C6~C30 Aromatically substituted pyridyl;

[0024] Alternatively, the A is selected from a group having a structure of formula Ab;

[0025]

[0026] Wherein, the R9 is selected from unsubstituted C1~C 20 Aromatic, cyano-substituted C1~C 20 Aromatic, trifluoromethyl substituted C1~C 20 Aromatic group;

[0027] Alternatively, the A is selected from a group having a structure of formula Ac;

[0028]

[0029] Among them, the R 10 and R 11 Independently selected from C1 to C 20 An aromatic group, and the R 10 and R 11 and B in which they are located form a ring or not, the R 10 and the B where it is located and the phenyl group where B is located form a ring or not, R 11 and the B where it is located and the phenyl group where B is located may or may not form a ring. Specifically, the R 10 and R 11 and the Bs in which they are located form a six-membered ring or no ring, the R 10 and the B where it is located and the phenyl group where B is located form a six-membered ring or no ring, R 11 and the B where it is located and the phenyl group where B is located form a six-membered ring or no ring. More specifically, the R 10 and R 11 and the Bs thereof form a six-membered heterocyclic ring or no ring, the R 10 and the B where it is located and the phenyl group where B is located form a six-membered heterocyclic ring or no ring, R 11 and B where it is located and the phenyl group where B is located form a six-membered heterocyclic ring or no ring; the heterocyclic ring is an oxygen-containing heterocyclic ring.

[0030] More preferably, A has the structures shown in Formula A-1, Formula A-2, Formula A-3, Formula A-4, Formula A-5, Formula A-6, Formula A-7, Formula A-8, Formula A-9, Formula A-10, Formula A-11 and Formula A-12:

[0031]

[0032]

[0033] Among them, R12 Independently selected from C1 to C 20 Alkyl or C6~C 30 Aromatic group.

[0034] The number average molecular weight M of the blue thermally induced delayed fluorescent polymer of the present invention is n In certain embodiments of the present invention, the blue thermally induced delayed fluorescent polymer is a polymer having a structure shown in formula (Ia), formula (Ib), formula (Ic), formula (Id), formula (Ie), formula (If), formula (Ig), formula (Ih), formula (Ii) or formula (Ij);

[0035]

[0036]

[0037]

[0038]

[0039] Among them, -C8H in Formula Ia to Formula Ij 17 All represent n-octyl, and the -C6H 13 All represent n-hexyl.

[0040] In some embodiments of the present invention, the blue thermally induced delayed fluorescence polymer has a capping group, and the capping group is a phenyl group, which is a polymer having a structure shown in formula (I-1), formula (I-2), formula (I-3), formula (I-4), formula (I-5), formula (I-6), formula (I-7), formula (I-8), formula (I-9) or formula (I-10);

[0041]

[0042]

[0043]

[0044]

[0045] Among them, C8H in Formula I-1 to Formula I-10 17 All represent n-octyl, and the C6H 13 All represent n-hexyl.

[0046] The present invention also provides a method for preparing the blue thermally induced delayed fluorescent polymer described in any of the above technical solutions, comprising the following steps:

[0047] The compound having the structure of formula B, the compound having the structure of formula M and the compound having the structure of formula N are polymerized to obtain a blue thermally induced delayed fluorescent polymer having the structure of formula 1;

[0048]

[0049] The X1 is selected from pinacol borate, boric acid, methyltin or butyltin, preferably pinacol borate;

[0050] Said X2 and X3 are independently selected from Br or I, preferably Br;

[0051] Wherein, the R1 to R7 and A are the same as those described above and will not be described in detail. Preferably, the compound having the structure of formula Ba, the compound having the structure of formula Ma and the compound having the structure of formula Na are polymerized to obtain a blue thermally induced delayed fluorescent polymer having the structure of formula 1;

[0052]

[0053] Among them, the R1 to R7 and A are the same as above and will not be repeated here.

[0054] The present invention first polymerizes a compound having a structure of formula B, a compound having a structure of formula M, and a compound having a structure of formula N. Specifically, under a protective gas atmosphere, a compound having a structure of formula B, a compound having a structure of formula M, and a compound having a structure of formula N are mixed in an organic solvent for polymerization reaction to obtain a blue thermally induced delayed fluorescent polymer having a structure of formula 1. The present invention has no special requirements for the conditions of copolymerization, and any copolymerization method known in the art can be used, wherein the catalyst for the copolymerization is preferably a palladium catalyst, more preferably a divalent palladium catalyst, and most preferably a di(tri-o-methylphenylphosphine)palladium dichloride (Pd[P(o-tol)3]2Cl2) and tri(dibenzylideneacetone)dipalladium (Pd2(dba)3) / 2-dicyclohexylphosphine-2′,6′-dimethoxybiphenyl (SPhos) catalyst.

[0055] After the polymerization, the product obtained by the reaction can be capped to obtain a blue thermally induced delayed fluorescent polymer having the structure of formula 1-a. The present invention has no special limitation on the capping method, which is a capping method well known to those skilled in the art.

[0056] The present invention also provides an organic electroluminescent device, comprising a first electrode, a second electrode and an organic layer between the first electrode and the second electrode, wherein the organic layer contains the blue thermally induced delayed fluorescence polymer described in any of the above technical solutions.

[0057] The present invention provides a blue thermally induced delayed fluorescence polymer and a preparation method and application thereof. The polymer having a structure of Formula 1 provided by the present invention has diphenylsilane and acridine in a TADF light-emitting unit directly connected, sp 3 The hybridized silicon atom can effectively interrupt the conjugation of the polymer main chain and improve the triplet energy level. When an alkyl substituent is introduced at the ortho position of the diphenylsilicon and TADF unit connection site, the torsion angle of the aromatic ring can be increased, the triplet energy level can be further increased, and the energy level difference between the singlet and triplet states can be reduced. At the same time, the increase in molecular rigidity inhibits non-radiative transitions. The experimental results show that this type of polymer not only has a high triplet energy level, but also has a high fluorescence quantum efficiency, presenting efficient blue thermally induced delayed fluorescence emission. In addition, the polymer preparation method provided by the present invention is simple, and the obtained polymer has excellent solubility and film-forming properties, and is expected to be applied to solution-processed electroluminescent devices to achieve industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is the fluorescence spectra of the polymers of Examples 1 to 5 in toluene solution;

[0059] Figure 2 is the fluorescence spectra of the polymers of Examples 6 to 10 in toluene solution;

[0060] Figure 3 The film-state fluorescence spectra of the polymers of Examples 1 to 5;

[0061] Figure 4 The film-state fluorescence spectra of the polymers of Examples 6 to 10;

[0062] Figure 5 are transient attenuation spectra of the polymer films of Examples 1 to 5 in an argon atmosphere;

[0063] Figure 6 The transient attenuation spectra of the polymer films of Examples 6 to 10 in an argon atmosphere. DETAILED DESCRIPTION

[0064] The present invention discloses a blue thermally induced delayed fluorescent polymer and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0065] The present invention will be further described below in conjunction with embodiments:

[0066] Example 1

[0067] Synthesis of polymer I-1:

[0068] (1) Preparation of bis(4-boronic acid pinacol ester phenyl) diphenylsilane

[0069] The reaction formula is as follows:

[0070]

[0071] The specific steps are as follows: under argon environment, di(4-bromophenyl)diphenylsilane (1mmol, 0.49g) is dissolved in 10mL THF, cooled to -78°C, and n-butyllithium (1.2mL, 3mmol) is added dropwise. After reacting at -78°C for 1 hour, isopropoxyboronic acid pinacol ester (0.8mL, 4mmol) is added to the reaction system, and the mixture is naturally returned to room temperature. The reaction is allowed to proceed overnight, and 10mL of deionized water is added to quench the mixture. The mixture is extracted with ethyl acetate, and the organic phase is washed with water for 3 times, dried over anhydrous sodium sulfate, filtered, and the solvent is removed by distillation under reduced pressure to obtain a crude product. The crude product is recrystallized from ethanol to obtain 0.35g of di(4-boronic acid pinacol ester phenyl)diphenylsilane with a yield of 60%. 1 H NMR (500MHz, CDCl3) δ7.83-7.78(m,4H),7.59-7.56(m,4H),7.55(dd,J=8.0,1.4Hz,4H),7.45-7.40(m,2H),7.39-7.34(m,4H),1.35(s,24H). 13 C NMR (126MHz, CDCl3) δ137.57,136.39,135.66,133.86,129.61,127.86,83.84,30.93,24.86.

[0072] (2) Synthesis of polymer I-1

[0073] The reaction formula is as follows:

[0074]

[0075] The specific steps are as follows: Under argon atmosphere, M1 (1.0 mmol, 0.588 g), M2 (0.10 mmol, 0.077 g), M3 (0.90 mmol, 0.507 g) and Pd[P(o-tol)3]2Cl2 (0.05 mmol, 40 mg) are dissolved in a dry 8 mL THF solution, heated to 75 °C and stirred for 0.5 hours, and a 2 M potassium phosphate aqueous solution (1.5 mL) after deoxygenation is added. After reflux reaction for 18 hours, a phenylboric acid solution (15 mg / 2 mL) dissolved in tetrahydrofuran is added and the reaction is continued for 5 hours, and then 1 mL of bromobenzene solution is added and the reaction is continued for 5 hours, and then a sodium diethylaminothiocarbamate chelating agent (1 g / 15 mL) dissolved in water is added and the reaction is continued for 10 hours. After the reaction was cooled to room temperature, deionized water was added to quench it, and it was extracted with dichloromethane. The organic phase was washed three times with deionized water, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to about 2 mL. It was added dropwise to methanol to precipitate a polymer, filtered, and extracted with acetone for 24 hours. The residue was collected, dissolved again in a small amount of dichloromethane, and precipitated in methanol to obtain 0.54 g of the target polymer I-1 with a yield of 63%.

[0076] GPC measurement of number average molecular weight M n It is 4.2 kDa, and the molecular weight distribution index PDI is 1.80;

[0077] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0078] Example 2

[0079] Synthesis of polymer I-2:

[0080] The reaction formula is as follows:

[0081]

[0082] The specific steps are similar to those of polymer I-1, except that the polymerization monomer feed ratio M1:M2:M3 is changed to 1:0.2:0.8, and 0.58 g of polymer I-2 is obtained with a yield of 62%.

[0083] GPC measurement of number average molecular weight M n It is 4.1 kDa, and the molecular weight distribution index PDI is 1.87;

[0084] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0085] Example 3

[0086] Synthesis of polymer I-3:

[0087] The reaction formula is as follows:

[0088]

[0089] The specific steps are similar to those of polymer I-1, except that the polymerization monomer feed ratio M1:M2:M3 is changed to 1:0.4:0.6, and 0.56 g of polymer I-3 is obtained with a yield of 57%.

[0090] GPC measurement of number average molecular weight M n It is 5.6 kDa, and the molecular weight distribution index PDI is 1.82;

[0091] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0092] Example 4

[0093] Synthesis of polymer I-4:

[0094] The reaction formula is as follows:

[0095]

[0096] The specific steps are similar to those of polymer I-1, except that the polymerization monomer feed ratio M1:M2:M3 is changed to 1:0.6:0.4, and 0.62 g of polymer I-4 is obtained with a yield of 61%.

[0097] GPC measurement of number average molecular weight M n It is 6.3 kDa, and the molecular weight distribution index PDI is 1.73;

[0098] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0099] Example 5

[0100] Synthesis of polymer I-5:

[0101] The reaction formula is as follows:

[0102]

[0103] The specific steps are similar to those of polymer I-1, except that the monomer feed ratio M1:M2:M3 is changed to 1:0.8:0.2, and 0.70 g of polymer I-5 is obtained with a yield of 66%.

[0104] GPC measurement of number average molecular weight M n It is 7.0 kDa, and the molecular weight distribution index PDI is 1.74;

[0105] Among them, C8H 17 is n-octyl, C6H13 It is n-hexyl.

[0106] Example 6

[0107] Synthesis of polymer I-6:

[0108] (1) Synthesis of bis(4-bromo-3-methylphenyl)diphenylsilane

[0109] The reaction formula is as follows:

[0110]

[0111] The specific steps are as follows: under argon environment, 1-bromo-4-iodo-2-methylbenzene (44mmol, 6.3mL) and dry 70mL tetrahydrofuran are added to a 250mL reaction bottle, cooled to -78°C, n-butyl lithium (45mmol, 18mL) is added dropwise, and the reaction is carried out at -78°C for 1 hour. Then dichlorodiphenylsilane (20mmol, 4.3mL) is slowly added, the reaction system gradually returns to room temperature, and the reaction is carried out for 10 hours. Deionized water is added to quench the reaction, and the reaction is extracted with dichloromethane. After the organic phase is washed three times with water, it is dried with anhydrous sodium sulfate, filtered, and distilled under reduced pressure to obtain a crude product. The obtained crude product is purified and separated by silica gel column chromatography to obtain 8.32g of di(4-bromo-3-methylphenyl)diphenylsilane, with a yield of 80%. 1 H NMR (500MHz, CDCl3) δ7.59-7.50(m,6H),7.50-7.43(m,2H),7.43-7.35(m,6H),7.20(dd,J=7.9,1.2Hz,2H),2.38(s,6H). 13 C NMR (126MHz, CDCl3) δ138.43,137.46,136.25,135.17,133.35,133.08,132.00,129.87,128.03,127.46,22.98.

[0112] (2) Synthesis of bis(4-boronic acid pinacol ester-3-methylphenyl)diphenylsilane

[0113] The reaction formula is as follows:

[0114]

[0115] The specific steps are as follows: under argon atmosphere, di(4-bromo-3-methylphenyl)diphenylsilane (1mmol, 0.52g) is dissolved in 10mL THF, cooled to -78°C, n-butyl lithium (1.2mL, 3mmol) is added dropwise, reacted at -78°C for 1 hour, isopropoxyboronic acid pinacol ester (0.8mL, 4mmol) is added to the reaction system, reacted for 8 hours, quenched with water, extracted with ethyl acetate, the organic phase is washed with water 3 times, dried over anhydrous sodium sulfate, filtered and distilled under reduced pressure to obtain a crude product. Ethanol recrystallization gives 0.37g of di(4-boronic acid pinacol ester-3-methylphenyl)diphenylsilane, with a yield of 60%. 1 H NMR (500MHz, CDCl3) δ7.74 (d, J = 7.3Hz, 2H), 7.56-7.51 (m, 4H), 7.43-7.38 (m, 2H), 7.38-7.31 (m, 8H), 2.48 (s, 6H), 1.34 (s, 24H). 13 C NMR (126MHz, CDCl3) δ143.67,137.55,137.02,136.43,134.80,134.20,132.82,129.47,127.78,83.50,24.90,22.33.

[0116] (3) Preparation of polymer 1-6

[0117] The reaction formula is as follows:

[0118]

[0119] The specific steps are as follows: Under argon environment, M4 (1mmol, 0.616g), M2 (0.10mmol, 0.077g) and M3 (0.90mmol, 0.507g) are dissolved in a dry 8mL THF solution, and a catalyst Pd2(dba)3 (0.05mmol, 46mg) and a phosphine ligand Sphos (0.20mmol, 82mg) are added, and the temperature is gradually raised to 75°C and stirred for 0.5 hours, and a 2M potassium phosphate aqueous solution (1.5mL) after deoxygenation is added. After reflux reaction for 18 hours, a phenylboric acid solution (15mg / 2mL) dissolved in tetrahydrofuran is added and the reaction is continued for 5 hours, and then 1mL of bromobenzene solution is added and the reaction is continued for 5 hours, and then a sodium diethylaminothiocarbamate chelating agent (1g / 15mL) dissolved in water is added and the reaction is continued for 10 hours. After the reaction was cooled to room temperature, deionized water was added to quench it, and it was extracted with dichloromethane. The organic phase was washed three times with deionized water, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure to about 2 mL. It was added dropwise to methanol to precipitate a polymer, filtered, and extracted with acetone for 24 hours. The residue was collected, dissolved again in a small amount of dichloromethane, and precipitated in methanol to obtain 0.68 g of the target polymer I-6 with a yield of 72%.

[0120] GPC measurement of number average molecular weight M n It is 5.3 kDa, and the molecular weight distribution index PDI is 1.87;

[0121] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0122] Example 7

[0123] Synthesis of polymer I-7:

[0124] The reaction formula is as follows:

[0125]

[0126] The specific steps are similar to those of polymer I-6, except that the polymerization monomer feed ratio M4:M2:M3 is changed to 1:0.2:0.8, and 0.75 g of polymer I-7 is obtained with a yield of 78%.

[0127] GPC measurement of number average molecular weight M n It is 4.3 kDa, and the molecular weight distribution index PDI is 1.81;

[0128] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0129] Example 8

[0130] Synthesis of polymer I-8:

[0131] The reaction formula is as follows:

[0132]

[0133] The specific steps are similar to those of polymer I-6, except that the polymerization monomer feed ratio M4:M2:M3 is changed to 1:0.4:0.6, and 0.73 g of polymer I-8 is obtained with a yield of 72%.

[0134] GPC measurement of number average molecular weight M n The molecular weight distribution index (PDI) is 7.0 kDa and 1.74.

[0135] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0136] Example 9

[0137] Synthesis of polymer I-9:

[0138] The reaction formula is as follows:

[0139]

[0140] The specific steps are similar to those of polymer I-6, except that the polymerization monomer feed ratio M4:M2:M3 is changed to 1:0.6:0.4, and 0.89 g of polymer I-9 is obtained with a yield of 85%.

[0141] GPC measurement of number average molecular weight M n It is 4.7 kDa, and the molecular weight distribution index PDI is 1.91;

[0142] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0143] Example 10

[0144] Synthesis of polymer I-10:

[0145] The reaction formula is as follows:

[0146]

[0147] The specific steps are similar to those of polymer I-6, except that the polymerization monomer feed ratio M4:M2:M3 is changed to 1:0.8:0.2, and 0.83 g of polymer I-10 is obtained with a yield of 76%.

[0148] GPC measurement of number average molecular weight M n It is 5.9 kDa, and the molecular weight distribution index PDI is 1.82;

[0149] Among them, C8H 17 is n-octyl, C6H 13 It is n-hexyl.

[0150] Comparative Example 1

[0151] Polymer molecular structure:

[0152]

[0153] GPC measurement of number average molecular weight M n It is 13.0 kDa, and the molecular weight distribution index PDI is 2.2;

[0154] Among them, C2H5 is ethyl, C5H 11 It is n-pentyl.

[0155] Embodiment 11

[0156] Photophysical properties determination:

[0157] The luminescent properties of the polymers obtained in Examples 1 to 10 of the present invention and the polymer of Comparative Example 1 were tested. The results are shown in Figure 1 to Figure 4 ,in, Figure 1 is the fluorescence spectra of the polymers of Examples 1 to 5 in toluene solution, Figure 2 is the fluorescence spectra of the polymers of Examples 6 to 10 in toluene solution, Figure 3 is the film-state fluorescence spectra of the polymers of Examples 1 to 5, Figure 4 The film-state fluorescence spectra of the polymers of Examples 6 to 10 are shown.

[0158] The test results are shown in Table 1, which shows the luminescence performance test results of the polymers described in Examples 1-10 of the present invention and the polymer of Comparative Example 1. ma x is the peak value of fluorescence emission in the membrane state; E T is the first triplet excited state energy level; ΔE ST Calculated from fluorescence and phosphorescence spectra; PLQY is the luminescence quantum efficiency of the polymer film in an argon atmosphere. From the test results, it can be seen that reasonable design of the main chain comonomer, TADF luminescent unit and polymerization method can achieve blue fluorescence emission, and these polymers have a higher triplet energy level and a very small ΔE ST , which is sufficient to achieve thermally induced delayed fluorescence and maintain a high PLQY.

[0159] Figure 5 is the transient attenuation spectra of the polymer films of Examples 1 to 5 in an argon atmosphere, Figure 6 The transient decay spectra of the polymer films of Examples 6 to 10 in an argon atmosphere. The transient decay spectrum test results show that the luminescence mechanism of the polymer contains short-lived instantaneous emission and long-lived delayed emission, indicating that it has thermally induced delayed fluorescence. For example, the instantaneous luminescence lifetime of the polymer shown in Example 8 shown in Table 1 is 19ns (accounting for 27%), the delayed luminescence lifetime is 10.7μs (accounting for 77%), the film fluorescence quantum efficiency is close to 100%, and its emission wavelength is at 473nm, achieving efficient blue thermally induced delayed fluorescence emission.

[0160] The luminescence spectrum of the polymer of Comparative Example 1 was tested, and the results showed that its emission wavelength was at 514 nm. This is because when the carbazole unit is directly connected to the TADF unit, the degree of conjugation of the polymer main chain is increased, causing the spectrum to red-shift and the triplet energy level to decrease to 2.53 eV, which is significantly lower than the polymer described in the present invention in which the diphenylsilicon unit is directly connected to the TADF unit (2.74~2.90 eV).

[0161] Table 1

[0162]

[0163] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A blue thermally induced delayed fluorescent polymer having a structure of formula 1: in, The R1 and R3 are independently selected from C6 to C 30 Aromatic group; Said R2 and R4 are independently selected from H or C1-C8 alkyl; The R5, R6 and R7 are independently selected from C1 to C 20 Alkyl or C6~C 30 Aromatic group; The A is selected from C6~C 50 Aromatic group; The n is 2 to 200; The 0 <x<0.5。 2. The blue thermally induced delayed fluorescence polymer according to claim 1, characterized in that: The A is selected from a group having a structure of formula Aa; Wherein, R8 is selected from unsubstituted triazine group, cyano substituted triazine group, trifluoromethyl substituted triazine group, C1~C 20 Alkyl-substituted triazine, C6~C 30 Aromatically substituted triazine radicals, unsubstituted pyrimidinyl radicals, cyano-substituted pyrimidinyl radicals, trifluoromethyl-substituted pyrimidinyl radicals, C1-C 20 Alkyl-substituted pyrimidinyl, C6~C 30 aromatic substituted pyrimidinyl, unsubstituted pyridyl, cyano substituted pyridyl, trifluoromethyl substituted pyridyl, C1~C 20 Alkyl substituted pyridyl, C6~C 30 Aromatically substituted pyridyl; Alternatively, the A is selected from a group having a structure of formula Ab; Wherein, the R9 is selected from unsubstituted C1~C 20 Aromatic, cyano-substituted C1~C 20 Aromatic, trifluoromethyl substituted C1~C 20 Aromatic group; Alternatively, the A is selected from a group having a structure of formula Ac; Among them, the R 10 and R 11 Independently selected from C1 to C 20 An aromatic group, and the R 10 and R 11 and B in which they are located form a ring or not, the R 10 and the B where it is located and the phenyl group where B is located form a ring or not, R 11 and the B where it is located and the phenyl group where B is located may or may not form a ring.

3. The blue thermally induced delayed fluorescence polymer according to claim 2, characterized in that: The A has the structures of formula A-1, A-2, A-3, A-4, A-5, A-6, A-7, A-8, A-9, A-10, A-11 and A-12: Among them, R 12 Independently selected from C1 to C 20 Alkyl or C6~C 30 Aromatic group.

4. The blue thermally induced delayed fluorescence polymer according to claim 1, characterized in that: The R2 and R4 are independently selected from H, methyl, ethyl, propyl, butyl, pentyl or hexyl.

5. The blue thermally induced delayed fluorescence polymer according to claim 4, characterized in that: The R2 and R4 are both methyl groups.

6. The blue thermally induced delayed fluorescence polymer according to claim 1, characterized in that: The R1 and R3 are independently selected from unsubstituted C6 to C 30 Aromatic group, or C1~C 20 Alkyl and C1~C 20 At least one substituted C6-C 30 Aromatic group; The R5, R6 and R7 are independently selected from unsubstituted C1 to C 20 Alkyl, unsubstituted C6~C 30 Aromatic group, or C1~C 20 Alkyl and C1~C 20 At least one substituted C6-C 30 Aromatic group.

7. The blue thermally induced delayed fluorescence polymer according to claim 6, characterized in that: Said R1 and R3 are independently selected from phenyl, tolyl, ethylphenyl, butylphenyl, hexylphenyl, octylphenyl, methoxyphenyl or dimethylaminophenyl; The R5 is selected from hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, butylphenyl, hexylphenyl, octylphenyl, decylphenyl, undecylphenyl, tridecylphenyl, heptadecylphenyl, hexyloxyphenyl, octyloxyphenyl, decyloxyphenyl, undecyloxyphenyl, tridecyloxyphenyl or heptadecyloxyphenyl; The R6 and R7 are independently selected from methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl, methylphenyl, butylphenyl, hexylphenyl, octylphenyl, decylphenyl, methoxyphenyl, hexyloxyphenyl, octyloxyphenyl or decyloxyphenyl.

8. The blue thermally induced delayed fluorescence polymer according to claim 1, characterized in that: It is a polymer having a structure of Formula (Ia), Formula (Ib), Formula (Ic), Formula (Id), Formula (Ie), Formula (If), Formula (Ig), Formula (Ih), Formula (Ii) or Formula (Ij); 9. The method for preparing the blue thermally induced delayed fluorescent polymer according to any one of claims 1 to 8, characterized in that: The following steps are involved: The compound having the structure of formula B, the compound having the structure of formula M and the compound having the structure of formula N are polymerized to obtain a blue thermally induced delayed fluorescent polymer having the structure of formula 1; The X1 is selected from pinacol borate, boric acid, methyltin or butyltin; The X2 and X3 are independently selected from Br or I.

10. A light emitting device, characterized in that The invention comprises a first electrode, a second electrode and an organic layer between the first electrode and the second electrode, wherein the organic layer contains the blue thermally induced delayed fluorescent polymer according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Heat-inducible delayed fluorescence polymer with main chain comprising diphenyl silane and carbazole unit and preparation method of heat-inducible delayed fluorescence polymer

    CN108383980A

  • Heat-induced fluorescence-delaying compound as well as preparation method and application thereof

    CN109810097A

  • Structure-clear thermally activated delayed fluorescence conjugated polymer and preparation method and application thereof

    CN110776623A

  • Organic electroluminescent device and display apparatus

    WO2022257817A1